2021
DOI: 10.1186/s43019-021-00095-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender, age, and body mass index on the medial and lateral posterior tibial slopes: a magnetic resonance imaging study

Abstract: Background The posterior tibial slope (PTS) is crucial in knee joint stability and in maintaining the natural movement of the knee. An increase in the PTS is associated with various knee pathologic conditions, such as anterior cruciate ligament (ACL) injury and anterior tibial translation (ATT). In the present study, we aimed to establish native medial and lateral PTS values for adult Saudis and to identify any association between PTS and gender, age, and body mass index (BMI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Medda et al [ 53 ] found that there was no significant correlation between the PTS and sex in studies in the Indian population. In the present study, there were no significant differences in the PTS between the left and right sides ( P > 0.05), similar to the findings reported by Kacmaz et al [ 9 , 18 , 54 ]. Our study found that PTS differed among different age groups with some regularity, which was similar to the findings of Sun et al [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Medda et al [ 53 ] found that there was no significant correlation between the PTS and sex in studies in the Indian population. In the present study, there were no significant differences in the PTS between the left and right sides ( P > 0.05), similar to the findings reported by Kacmaz et al [ 9 , 18 , 54 ]. Our study found that PTS differed among different age groups with some regularity, which was similar to the findings of Sun et al [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Medda et al [33] found that there was no signi cant correlation between the PTS and sex in studies including Indians. In this study, there were no signi cant differences in the PTS between the left and right sides (P>0.05), and these ndings were similar to those reported by Kacmaz et al [8,14,15]. In this study, the difference in the PTS between the different age groups was not affected by sex.…”
Section: Discussionsupporting
confidence: 91%
“…Osteoarthritis (OA) has a multifactorial etiology, including aging, obesity, previous injury, female, hormone level, and epigenetics [1][2][3]. The articular cartilages receive their nutrients by synovial fluid infiltration, which make it difficult for the cartilage to repair after injury [4,5].…”
Section: Introductionmentioning
confidence: 99%